Efficacy of Edible Coating to Extend the Post-harvest Shelf-life of Shallot (Allium ascalonicum) Bulb - N. P. Minh (Journal of Global Pharma Technology, 2019)
Shallot or violet onion (Allium ascalonicum) bulbs are well known for their biological activity resulting from the presence of sulphur compounds. The health and nutritional benefits of shallot have led to their increased demand and hence production. Shallot harvest handling must be done immediately after harvest because these commodity are easily damaged. Plastic food packaging causes serious environmental problems. Edible coatings offer various physicochemical advantages for fruit and vegetable in preservation. Objective of this study focused on the effectiveness of different coating materials such as chitosan, CMC, xanthan gum, carrageenan, sodium alginate to the quality of shallot bulbs. Results showed that after 6 month storage by 3.0% chitosan at ambient temperature, shelf-life of shallot bulbs remained its stability. Edible coating could maitain shallot quality by controlling respiration rate as well as decay. It’s not only as an effective strategy for the product but also friendly environment.Keywords: Shallot bulb, Allium ascalonicum, Chitosan, Coating, Storage, Shelf-life.